A framework for product development based on recycled plastic from pesticide packaging: A study of short supply chains from the perspective of circular economy - Paschoal José de Pilla, Jr.; Márcio Lopes Pimenta; Bruno Garcia de Oliveira (Cleaner Production Letters, 2024)
The global shift towards circular economies has emphasized the need to rethink traditional supply chains, particularly in industries with high waste outputs, like plastics. This study argues that the implementation of Short Supply Chains (SSC) for the plastic recycling process, particularly for pesticide packaging, can create added value. Therefore, this paper aims to characterize the concept of Short Supply Chain in the context of circular plastic product development, with a focus on recycling and regional commercialization. A case study was conducted with a Brazilian pesticide supply chain. Brazil is one of the world's largest food producers and pesticide users. Key actors in the reverse logistics process were interviewed, and the data were supplemented with information from industry reports. Through content analysis, the key findings reveal how implementing a short supply chain can generate value across three main categories: the scale of waste recovery, development of circular products, and legal considerations. Propositions were developed as theoretical implications for each category and integrated into a novel conceptual framework. By cross-referencing propositions with practical implications, research opportunities were identified on how short supply chains can promote the circularity of pesticide packaging.